Recovery of damaged high-Arctic vegetation under climate change - Lærke Stewart; Peter Aastrup (Arctic, Antarctic, and Alpine Research)
Human disturbance in the Arctic is increasing. Abrupt changes in vegetation may be expected, especially when spots without vegetation are made available; additionally, climate change alters competition between species. We studied whether 34- to 35-year-old seismic operations had left imprints on local vegetation and whether changes could be related to different soil characteristics. The study took place in Jameson Land in central east Greenland where winter seismic operations in search of oil took place from 1985 to 1989. This area is dominated by continuous dwarf shrub heath with Cassiope tetragona, Betula nana, and Vaccinium uliginosum as dominant species. Using point frame analyses, we registered vascular plants and other surface types in frames along 10-m transects in vehicle tracks (hereafter “damages”) and in undisturbed vegetation parallel to the track (hereafter “references”) at eleven study sites. We also measured temperature and pH and took soil samples for analysis. Damaged and reference vegetation types were compared with Sørensen similarity indices and detrended correspondence analyses. Although most vascular plant species were equally present in damaged vegetation and in references the detrended correspondence analyses showed that at ten out of eleven study sites the damages and references still differed from each other. Graminoids and the herb Polygonum viviparum had the highest occurrence in damages. Shrubs and the graminoid Kobresia myosuroides had the highest occurrence in references. Cassiope tetragona was negatively impacted where vehicles had compacted the snow. Moss, organic crust or biocrust, soil, and sand occurred more often in damages than in references, whereas lichens and litter had the highest occurrence in references. The richness of vascular plant species varied between the eleven study sites, but between damages and references the difference was only up to four species. Temperature was the soil parameter with the most significant differences between damages and references. Total recovery of the damaged vegetation will most likely not occur within several decades. The environmental regulations were important to avoid more serious impacts.